2018
DOI: 10.3390/jcm7100326
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rehabilitation on Outcomes after TAVI: A Preliminary Study

Abstract: The benefit of rehabilitation in elderly patients undergoing transcatheter aortic valve implantation (TAVI) for treatment of severe aortic stenosis is unknown. The impact of declining rehabilitation programs on mortality has also not been described. In a longitudinal cohort study of 1056 patients undergoing elective TAVI between 2008 and 2016, logistic regression analysis was used to assess the relationship between treatment modality and outcome according to whether or not patients participated in a three-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
1
23
0
8
Order By: Relevance
“…In Germany, multicomponent CR represents a wellestablished treatment for the improvement of functional and psychocognitive parameters in patients after cardiac valve procedures [12][13][14][15]. For elderly patients, there is also the option of being allocated to geriatric rehabilitation (GR) instead of indication-specific rehabilitation, if there are at least two different indications to be treated.…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, multicomponent CR represents a wellestablished treatment for the improvement of functional and psychocognitive parameters in patients after cardiac valve procedures [12][13][14][15]. For elderly patients, there is also the option of being allocated to geriatric rehabilitation (GR) instead of indication-specific rehabilitation, if there are at least two different indications to be treated.…”
Section: Introductionmentioning
confidence: 99%
“…In this study the authors showed that each of PM, ET and RFM clearly reduce the hazard ratio of mortality and concluded that comprehensive CR has substantial benefits in reducing mortality and morbidity [14]. A recent study showed that elderly patients who attended a cardiac rehabilitation program after trans-catheter aortic valve implantation had decreased mortality at 6 months [15].…”
Section: Introductionmentioning
confidence: 80%
“…Die Evidenz von Schulungen zur Lebensstilintervention wird aufgezeigt und die Bedeutung der beruflichen Wiedereingliederung hervorgehoben [15]. [4].…”
Section: S3-leitlinie Kardiologische Rehabilitation Im Deutschsprachiunclassified
“…In der multivariaten Analyse waren nach 7 Jahren die Gesamtmortalität um über 40 % (HR 0,5768; 95 %-CI 0,5650-0,5888; p < 0,0001) und die Rehospitalisierung um 20 % (HR 0,7997; 95 %-CI 0,7758-0,8244; p < 0,0001) in der Gruppe mit KardReha im Vergleich zu den Patienten mit "usual care" signifikant reduziert [14]. [4]. Nach 6 Monaten war das Gesamtüberleben in der Reha-Gruppe signifikant höher als in der Kontrollgruppe (95,0 % vs. 89,8 %; p = 0,003).…”
Section: Koronare Herzerkrankungunclassified
See 1 more Smart Citation